Development Zoning of Bindu River Ecotourism based on Eco Culture - Eryani, I Gusti Agung Putu; Arthana, I Nyoman Nuri; Astiti, Ni Made Ayu Gemuh Rasa (Civil and Environmental Science Journal (CIVENSE), 2021)
Bindu River Ecotourism is a tourist attraction that has natural potential as a place of recreation in the Denpasar City area. Apart from the potential offered by Bindu River Ecotourism, there are still problems that exist in Bindu River Ecotourism including river water which has a lot of sediment, the lack of public awareness to care about the surrounding environment, and the lack of exposure by the public makes only the surrounding community aware of it. If zoning is not carried out in its development, the natural potential of the Bindu River Ecotourism area that has been arranged can be reduced, for this reason, zoning is needed in its development to determine areas in the Bindu River Ecotourism area that are in accordance with the land use and development potential. Based on the delineation and the existing potential, the Bindu River Ecotourism area is divided into a conservation zone and a recreation zone. For the conservation zone, it can be developed into several more zones in the upstream part, it can be developed into a zone for the development of the function of protecting water resources, a zone for the development of the function of protecting flora and fauna as well as limited recreational functions. While the recreation zone can also be developed into several more zones. The upstream recreation zone can be developed into a recreation function development zone and the downstream recreation zone can be developed into an educational function development zone.